CREATING VALUE IN A SERVICES SUPPLY CHAIN - Martins, A.; Crespo de Carvalho, J. (10th International Symposiumon Logistics, 2005)
Value creation is the basis for competition. Both service providers and manufactures must continuously adjust their offers to their customers’ specific needs. Public services are no different from other service providers in terms of need for value creation. The purpose of this paper is discussing the concept of value in terms of services, focussed on the court services. The court process will be mapped and bottlenecks will be identified. Two Portuguese Courts of First Instance will be used as case studies. Statistics will be used to compare data from 198 court cases. Results show that courts need to improve employees’ expertise, increase of the number of courtrooms, and redefine judge evaluation criteria in order to improve value for their customers. Limitations and topics for further research are discussed and identified.